Mediterranean Quercus suber wooded grasslands risk disappearance: New evidences from Sardinia (Italy) - Rossetti, Ivo; Bagella, Simonetta (Forest Ecology and Management, 2014)
Wooded grasslands are the most widespread agro-forestry systems in Europe, and are included in the Natura 2000 network due to their importance in biodiversity conservation. Similar to many man-made systems, long-term wooded grasslands conservation depends on sustainable use practices. Regeneration of the tree layer is indispensable to assure wooded grassland maintenance. Several studies in Spanish dehesas and Portuguese montados generated concerns regarding the long-term conservation of these agro-silvo-pastoral systems. In the present study, we tested if tree regeneration issues documented for the Iberian Peninsula also affected wooded grasslands located in another Mediterranean area inside and outside Natura 2000 network. The size structure of Quercus suber L. stands, and the abundance and height of seedlings and saplings were determined at farm and landscape scales, in grazed, grazed and tilled wooded grasslands, and non-grazed woodlands to test the compatibility of management type for tree regeneration. A frequency model of size structure was calculated to estimate the probability of cork oak stand survival in a medium and long term time period. New evidences of a generalised absence of regeneration in grazed wooded grasslands emerged from all the study sites. Some management practices are indicated for the long-term conservation of the habitat.
Keywords: Grazing; Habitat 6310; Natura 2000; Predictions; SIZE STRUCTURE; Tillage

Effects of long-term management practices on grassland plant assemblages in Mediterranean cork oak silvo-pastoral systems - Bagella, Simonetta; Salis, Lorenzo; Marrosu, Gian Marco; Rossetti, Ivo; Fanni, Stefania; Caria, Maria Carmela; Roggero, Pier Paolo (PLANT ECOLOGY, 2013)
The assessment of the effects of long-term management practices is relevant in understanding the current patterns of plant assemblages in semi-natural ecosystems. We hypothesized that the variety of management practices across different farming systems under the same ecological conditions directly and indirectly shapes these patterns via the long-term changes induced in soil features. The aims of this paper were to evaluate the influence of two sets of variables describing long-term management practices and soil features on plant assemblages and their importance in the context of Mediterranean silvo-pastoral systems. The analysis of variance revealed that richness and grazing value were not affected at all by grazing livestock species and soil tillage frequency and that they both showed relatively high absolute values for the specific context under study. Trifolium subterraneum was a key species in contributing to grassland grazing value and habitat biodiversity. The Canonical Correspondence Analysis highlighted the influence of management practices and soil features on plant assemblage composition, which was significantly affected by grazing livestock species and stocking rate and by soil pH and K content. The Redundancy Analysis showed that soil pH and related features were in turn affected by stocking rate, supporting our hypothesis that management practices influenced plant assemblage composition directly and indirectly via their long-term effects on soil features. The results also highlighted that a systemic analytical perspective applied at a grazing system scale can be effective in addressing sustainable grassland management issues in Mediterranean silvo-pastoral systems.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: grazing systems; soil features; Stocking rate; Tillage; Trifolium subterraneum